Os cotistas negros na universidade: perfis e representações - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
This research analyzed the development and the introduction of a quota program for black people on the quota politics in its first years of implementation at the State University of Ponta Grossa (UEPG). The research sought to describe the representations that the students from the quotas 1 (universal) and 3 (black people) have regarding to the quotas for black ones as well as to analyze the relationship that the quota black students have established in their social and academic life environment as with the professors as with their classmates in the University Course. The theoretical discussions were supported in such authors: Rüsen (1987 and 2006), Freire (1982, 1986, 1996), Cerri (2001) and Pacievitch (2007), Skliar and Dushatzky (2001), Rios (2005) and Silva and Silvério (2003), Henriques (2004), Chauí (2001), Siss (2003), Neves (2005), Carvalho (2004), Brandão (2005), Gomes (2001), Sá (1996) and Spink (1995). The basis methodology is the qualitative research since we emphasized the process in witch this politic was implemented. In the beginning of the process we used the qualitative research, which gave the research context, and we explored some graphics and charts with the students marks obtained in the 2006 and 2007 vestibulares (the University admission exam). We calculated the marks by quotas and the pattern diversion of each course relating to the quotas 3 and 1. We selected some courses from the UEPG in order to work with a sample. Then, we went to the qualitative research, in which the Historical Conscious was the base for the instruments elaboration, and the Social Representations Theory for analyze. Firstly we applied a questionnaire for all the students from the selected courses, following the analyses and the categorization of the questionnaires, and then we applied new questionnaires and interviews only for the quote black people from the same selected courses. We sought to look at the specific positive and negative effects of this politics instead of the pure product. The results allowed us to reveal that the quotas have helped the increase of the black and the public school students’ population at the university in 15%; witch percentage could be smaller without such quotas politic. Most of the students from UEPG are not aware about the affirmative politics and make their opinion about the black quotas based on their common sense. They associate the small quantity of black people at the university to the poor quality of the public teaching. The black students with quotas felt under discrimination into the course including by some professors that made their quota rejection clear. The different positions about the quotas can be considered by the Social Representations like old social representations of the black people in the society witch get in confront with the new representations that have been built by those that fight for the black people rights. Based in the questionnaires applied in the six courses of the UEPG and the questionnaires and the interview with the black people quotas was possible to construct the diagrams that referred to the students’ representations on the UEPG quotas. Thus, it is necessary to bear in mind that the acquisition of a Higher Education degree is not enough for eliminating the social and racial differences. The vacancies for the black population into the University program are not enough; in fact, the changing in the admission is just one aspect within a major process.
Keywords: cotas para negros; ensino superior; ações afirmativas; quotas for people; higher education; affirmative action; CNPQ::CIENCIAS HUMANAS::EDUCACAO